Zmiany okulistyczne w zespole Turnera - Urban, Beata; Bakunowicz-Łazarczyk, Alina (Klinika Oczna / Acta Ophthalmologica Polonica, 2005)
Authors present pathogenesis, clinical manifestations, ocular findings, diagnosis and treatment of patients with Turner's syndrome.